Enhancing Communication Skills for Studentpreneurs: A Training Program on Public Speaking: Meningkatkan Kemampuan Komunikasi untuk Mahasiswa Wirausaha: Program Pelatihan Berbicara di Depan Umum - Herachwati, Nuri; Isnaini, Santi; Agustina, Tri Siwi (Indonesian Journal of Law and Economics Review, 2023)
This research aimed to enhance the communication skills of studentpreneurs in the WEBS unit at Universitas Airlangga. Through a community engagement activity aligned with SDGs 4 and 8, a training program focused on public speaking skills was conducted. The two-day training in May 2023 resulted in notable improvements in participants' knowledge and skills. They displayed increased confidence, effective body language, eye contact, and improved delivery, all crucial for their entrepreneurial pursuits. The training received positive feedback, with high engagement and enthusiasm from participants and speakers. Pre- and post-test assessments revealed enhanced understanding of communication elements, cultural factors, and psychological aspects related to public speaking. Participants also demonstrated growth in public speaking abilities, showcasing greater boldness, facial expressions, vocal modulation, and originality in presenting ideas. The findings underscore the significance of practical application and continuous development of communication skills. This study offers valuable insights to researchers and professionals, providing an effective approach for enhancing communication competencies among studentpreneurs. Highlight: Community engagement activity targeting studentpreneurs within the WEBS unit at Universitas Airlangga, addressing communication weaknesses. Training program on public speaking resulting in increased knowledge, skills, confidence, and improved communication techniques. Positive outcomes demonstrated through high participant engagement, knowledge enhancement, and noticeable improvements in public speaking abilities. Keyword: WEBS, Communication Skills, Public Speaking, Studentpreneurs, Training Program